Prostate Cancer Antigen 3 Gene Expression in Peripheral Blood and Urine Sediments from Prostate Cancer and Benign Prostatic Hyperplasia Patients versus Healthy Individuals - Moradi Sardareh, Hemen; Goodarzi, Mohammad Taghi; Yadegar-Azari, Reza; Poorolajal, Jalal; Mousavi-Bahar, Seyed Habibollah; Saidijam, Massoud (Urology Journal, 2014)
Purpose: To determine the expression of prostate cancer antigen 3 (PCA3) gene in peripheral blood and urine sediments from patients with prostate cancer (PCa) and benign prostatic hyperplasia (BPH) and normal subjects. Materials and Methods: A total number of 48 patients [24 with biopsy proven prostate cancer (PCa) and 24 with benign prostate hyperplasia (BPH)] were studied. Twenty-four healthy individuals were also recruited as control group. After blood and urine sampling, total RNA was extracted and cDNA was synthesized. Expression of PCA3 gene was assessed by quantitative reverse transcription polymerase chain reaction. Results: Comparison of PCA3 gene expression between control and BPH groups indicated no statistically significant differences in both urine and blood samples. Patients with PCa demonstrated an increased PCA3 gene expression rate compared to control and BPH groups (10.64 and 7.17 folds, respectively). The rate of fold increased PCA3 gene expression in urine was 20.90, 20.90, and 20.35 in patients with PCa, BPH and normal subjects, respectively. Conclusion: Evaluation of PCA3 gene expression can be considered as a reliable marker for detection of PCa. Increased level of this marker in urine sediments is more sensitive than blood for distinguishing between cancerous and non-cancerous groups.